Evaluation of Rapidly Disintegrating Vaginal Tablets of Tenofovir, Emtricitabine and Their Combination for HIV-1 Prevention - Meredith R. Clark; M. Melissa Peet; Sarah Davis; Gustavo F. Doncel; David R. Friend (MDPI AG, 2014)
Vaginal tablets are being developed as an alternative to gels as an inexpensive, discreet dosage form for the administration of microbicides. This work describes the pharmacokinetic (PK) evaluation of rapidly disintegrating vaginal tablets containing tenofovir (TFV, 10 mg), emtricitabine (FTC, 10 mg), and the combination of TFV and FTC (10 mg each) under in vitro and in vivo conditions, and in direct comparison to the clinical TFV 1% gel, a microbicide product in Phase III clinical testing. The PK of TFV and FTC from tablets were also evaluated in female rabbits following intravaginal administration. Direct comparison of a single dose of TFV tablets (intact or predissolved at 10 mg/mL) and TFV 1% gel showed no differences in the vaginal PK of TFV between groups; however systemic bioavailability of TFV was significantly higher from the gel. When rabbits were dosed either once or daily for seven days with intact tablets of TFV, FTC, or the combination of TFV/FTC, vaginal and systemic concentrations of TFV and FTC were unaffected by co-formulation. Moreover, plasma PK parameters were similar following a single dose or seven once-daily doses. Tissue concentrations of TFV and FTC in the cranial vagina 4 h after administration ranged between 104 and 105 ng/g. Concentrations of TFV-diphospate (TFV-DP, the active metabolite) were also high (over 103 ng/g or about 3000 to 6000 fmol/mg) in the cranial vagina 4 h after administration and similar to those measured following administration of TFV 1% gel. These data demonstrate that rapidly disintegrating vaginal tablets may be a suitable topical microbicide dosage form providing similar vaginal TFV PK to that of TFV 1% gel. The data also support co-administration of FTC with TFV in a single vaginal tablet to create a combination microbicide in a simple and inexpensive dosage form.